2022
DOI: 10.1038/s41541-022-00547-0
|View full text |Cite
|
Sign up to set email alerts
|

CD4 T cell epitope abundance in ferritin core potentiates responses to hemagglutinin nanoparticle vaccines

Abstract: Nanoparticle vaccines based on H. pylori ferritin are increasingly used as a vaccine platform for many pathogens, including RSV, influenza, and SARS-CoV-2. They have been found to elicit enhanced, long-lived B cell responses. The basis for improved efficacy of ferritin nanoparticle vaccines remains unresolved, including whether recruitment of CD4 T cells specific for the ferritin component of these vaccines contributes to cognate help in the B cell response. Using influenza HA-ferritin nanoparticles as a proto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 70 publications
2
11
0
Order By: Relevance
“…However, vaccination strategies or adjuvants specifically to target the recall of CD4+ Tfh cells to enhance the GC and its products have been slow to develop beyond the preclinical stage. We found that specifically targeting the recall and expansion of memory antigen-specific CD4+ T cells induced an increase in GC Tfh and HA-specific GC B cells early compared to mice that lacked antigen-specific memory CD4+ T cell during primary influenza infection, indicating that our findings concur with previous studies that targeting CD4+ T cells is a successful strategy to enhance the GC reaction (40, 44, 107). While heterologous infection/immunization priming enhanced the early GC Tfh and GC B cell magnitude, we did not see increases in HA-specific antibody titers, but we did see selection for specific clones in the resultant B cell repertoires.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…However, vaccination strategies or adjuvants specifically to target the recall of CD4+ Tfh cells to enhance the GC and its products have been slow to develop beyond the preclinical stage. We found that specifically targeting the recall and expansion of memory antigen-specific CD4+ T cells induced an increase in GC Tfh and HA-specific GC B cells early compared to mice that lacked antigen-specific memory CD4+ T cell during primary influenza infection, indicating that our findings concur with previous studies that targeting CD4+ T cells is a successful strategy to enhance the GC reaction (40, 44, 107). While heterologous infection/immunization priming enhanced the early GC Tfh and GC B cell magnitude, we did not see increases in HA-specific antibody titers, but we did see selection for specific clones in the resultant B cell repertoires.…”
Section: Discussionsupporting
confidence: 91%
“…We further compared the numbers of HA-specific GC B cells to the number of GC Tfh cells and found that in the GP(1°)PR8(2°) group, there was a significantly higher number of HA-specific GC B cells to every GC Tfh cell ( Fig 3J ). These data suggest that while the number of GC Tfh cells in the GP(1°)PR8(2°) group were similar to the PR8(1°) group, the GC Tfh cells may be of a higher quality as to sustain support for higher numbers of HA-specific GC B cells, as has been previously suggested (41, 44). Together, these data suggest that heterologous priming with adjuvanted rGP immunization or LCMV infection significantly enhanced the early anti-influenza germinal center B cell response following influenza infection compared to primary influenza infection.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…Importantly, the single mouse strain lacking CD4 + T cell epitopes in the ferritin core (C57BL/6) did not display enhanced B or CD4 + T cell responses relative to the conventional trimer construct, showing that the ferritin core CD4 + T cell epitope composition is a central and requisite feature of its enhanced B cell immunogenicity of the ferritin nanoparticle. Thus, low CD4 + T cell activity can limit the high‐affinity B cell response to clinically relevant vaccines and this feature needs to be optimized in vaccination strategies designed to elicit robust B cell responses to multimeric viral antigens 90 …”
Section: Novel Approaches To Antiviral Vaccinesmentioning
confidence: 99%
“…[ 21 ] The self‐assembled ferritin, as a natural and safe biomaterial, has good biocompatibility, biodegradability, stability, and surface modifiability. [ 22 ] The antigen of interest can be fused with the N ‐terminal (Asp5) of the ferritin subunit, and subsequently, multiple antigens can be displayed on the surface of ferritin nanoparticles, thereby enhancing its immunogenicity. [ 23 ] Ferritin nanoplatforms have been widely used to display antigens from different pathogens, including IV, [ 24 ] enterovirus 71 (EV71), respiratory syncytial virus, [ 25 ] canine distemper virus, [ 26 ] and SARS‐CoV‐2.…”
Section: Introductionmentioning
confidence: 99%